STRATEGI KOMUNIKASI PEMASARAN KULINER MELALUI MEDIA SOSIAL INSTAGRAM PADA GRANDE GARDEN CAFÉ - Safira Dewi Purnama; Febriana Sapphire Sani (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
In today's digital era with the increasing number of internet users. Internet is a medium that can help ease every activity of each individual. This study aims to use a social media management framework as well as a strategic orientation framework to explore how food and beverage businesses can manage social media well. As one of the cafes in the Prigen area, East Java, of course, it has one strategy in marketing by using social media, one of which is Instagram. where the author chose this Grande Garden Café as the subject material in this study. because Grande Garden Café is an outlet that sells a variety of contemporary foods and beverages, from light snacks to heavy meals. Marketing communication built by this business is a marketing strategy using Positioning Branding according to Philip Kotler. By stating that the action in designing this product there is a marketing mix in order to create a certain impression. This company must understand the position of each competitor in order to determine the strategic direction in building Positioning. For the Grande Garden Café company, social media has a very important role in enhancing personal branding. Where in the use of social media Instagram, the company can focus more on how the content can be demanded, accepted, remembered, and liked, this of course needs to display or obtain an existing advantage from the company. It aims to be able to attract the interest of consumers. From the findings of this study, it is also stated that the influence of social media Instagram can increase high selling power and be one form of the right strategy for companies to maintain their characteristics even though they are in the midst of competitors from other food and beverage outlets.